Instalasi dan Evaluasi Sistem Peringatan Dini Banjir Berbasis Sensor Ultrasonik HC-SR04 dan Internet of Things (IoT) - Alfiani, Nofita; Rakhmadi, Frida Agung; Yatman, Su (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
Research on installation and evaluation of early warning systems based on the HC-SR04 ultrasonic sensor and the Internet of Things (IoT) has been successfully carried out. This study aimed to install and evaluate a flood early warning system based on the ultrasonic sensor HC-SR04 and IoT at a flood monitoring post, Boyong River Yogyakarta. Installation of a flood early warning system based on the HC-SR04 and IoT ultrasonic sensor was carried out by preparing tools and materials, connecting WiFi, and installing the system. Evaluation accuracy of the system was carried out by varying the distance between the sensor and the water surface, namely 5 cm - 200 cm with 5 cm intervals, while testing of precision and success were done by 10 times repeating for each distance variation. The results showed that flood early warning system based on ultrasonic sensor HC-SR04 and IoT has been successfully installed at the flood monitoring post, Boyong River Yogyakarta. In addition, the flood early warning system based on ultrasonic sensor HC-SR04 and IoT was successfully evaluated with an accuracy value 99.95%, repeatability precision 98.75%, reproducibility 99.27%, and success 89.50%.